2003
DOI: 10.1128/aac.47.4.1241-1250.2003
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in Genes Associated with Isoniazid Resistance in Mycobacterium tuberculosis

Abstract: Isoniazid (INH) is one of the primary chemotherapeutic and prophylactic drugs used against Mycobacterium tuberculosis, the causative agent of tuberculosis, which remains the leading single cause of death due to an infectious agent throughout the world. Recent studies indicate that the median rate of primary resistance to INH is 7.3% (range, 1.5 to 32%) and that the rates of acquired resistance range from 5.3 to 70% globally (9, 45). The overall rate of resistance to INH is 8.4% in the United States and has rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
262
3
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(283 citation statements)
references
References 44 publications
14
262
3
4
Order By: Relevance
“…INH resistance is related to mutation(s) in katG, inhA, and/or the promoter region of mabA-inhA (17,22,38,39). In the present study, we found 11 novel mutations and a CTA insertion at nt position 1170 in katG.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…INH resistance is related to mutation(s) in katG, inhA, and/or the promoter region of mabA-inhA (17,22,38,39). In the present study, we found 11 novel mutations and a CTA insertion at nt position 1170 in katG.…”
mentioning
confidence: 48%
“…Isolates carrying the T324P, L48Q, or M257T mutation and Ϫ15C3T upstream of mabA were resistant to INH. However, it is unclear whether T324P, L48Q, or M257T is related to INH resistance because the Ϫ15C3T upstream of mabA is known to confer INH resistance (10,22,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that a variety of single nucleotide polymorphisms in multiple genes are found exclusively in INHresistant clinical isolates. These genes are either involved in mycolic acid biosynthesis or are overexpressed as a response to the buildup or cellular toxicity of INH [5]. Up to the present, twenty-four polymorphisms have been published.…”
Section: Resultsmentioning
confidence: 99%
“…Deletions of, or missense mutations in, the katG gene have been associated with decreased susceptibility to INH in approximately 50% of clinical isolates of M. tuberculosis (Heym et al 1995, Ramaswamy et al 2003. It has recently been shown that the S315T KatG mutant, which is one of the most commonly encountered substitutions in clinical INH-resistant strains, has reduced affinity for INH, which would result in decreased drug activation and ensuing INH resistance (Yu et al 2003).…”
Section: Biosynthesis Of Mycolic Acids (Fas-ii System)mentioning
confidence: 99%